Spiritualitas Pelayanan dan Pewartaan di Dunia Digital oleh Kaum Religius dan Rohaniwan - Pradipta, Gregorius Dimas Arya; Tedjoworo, Hadrianus (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2022)
In Christianity, religious and priests express their respective spirituality in various unique ways, different from the laity. This article explores the emerging spiritualities in serving the faithful by way of evangelization in everyday life, especially those expressed in the contents spread over the digital world by Catholic religious and priests. Spirituality motivates them to create different ways of catechesis and evangelization and at the same time challenges and deepens their motivations, especially in the middle of today’s technological leaps. The author also proposes some practical recommendations for religious and priests in refreshing their interpretations of their respective spirituality in order to proclaim the Gospel to the ever-connected people in the world. Refreshing their motivations in serving the faithful in this digital age can particularly help them be faithful to the calling of the Lord. This article invites religious to recontextualize the spirituality of their respective congregation and priests to recontextualize the spirituality of their respective diocese. In this digital age, their works might be called a kind of contemporary digital catechesis that connects the faithful from all over the world and that continues the Church’s mission today.